The sustainable built environment : technical, managerial, legal and economic aspects - Sertyesilisik, Begum, Ed. Al Shamma'a, Ahmed, Ed (Palgrave , Macmillan, 2016)
The text adopts an interdisciplinary approach to address the huge challenges in creating a sustainable built environment. In a broad survey of critical issues it assesses procurement, cost modelling and management, sustainable buildings, low and zero carbon technologies, sustainability in utilities, and the law